Identifying Inefficiencies in a R&D Project Handover Process : A Case Study of the Mirka Power Tools Unit - Kanckos, Simon (My University, 2021)
This Master’s thesis was commissioned by the research and development unit Power Tools at Mirka Ltd. Mirka is a world leader in surface finishing technology and the Power Tools Unit develops and produces inter alia electrical and pneumatic sanders and polishers. The purpose of the thesis was to find inefficiencies in the project handover process, the process in which the responsibility of maintaining the product design is handed over from the Development Team to the Product Life Cycle Team within the Power Tools Unit. The process is only vaguely described in the product development process description and this has impacted the efficiency and quality of the project handovers negatively. The Power Tools Unit has experienced large growth during the latest years, and it is of high priority to ensure efficiency and quality in their processes. The study was conducted with a qualitative approach. The literature review discusses different aspects of process improvement methodologies with a focus on efficiency and quality in processes in R&D environments, and tools and methods to improve such processes. Semi-constructed interviews with 13 stakeholders were conducted with the goals to gain an understanding of the process, to find the factors negating the process efficiency and quality, and to be able to suggest improvements to the process. In the results section of the thesis, the issues and the inefficiencies with the current state of the process are listed. The major issues with the process were found to come from the earlier stages in the product development process and to be the results of the lack of standardization. This caused inefficiencies in the form of burdensome handover of documentation, immoderate information intake for the Product Life Cycle Team, and unclarities such as who handles project residues. Other factors also affected the handover process, such as the individuality of the projects and the organizational culture to some degree. SIPOC and Swimlane Flowcharts were used to visualize the current and a proposed future state of the process. Improvement suggestions were given based on the Lean process improvement methodology and the interview findings. A proposal to a project handover checklist is also included in the thesis. The Power Tools Unit may choose to adapt and standardize the proposed process and handover checklist, and the results from this thesis may also be used as material for eventual analysis of the entirety of the Power Tool Unit’s product development process.
Keywords: case study; product development; project management; product life cycle; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Systems Analytics